Liquid fuel oil produced from plastic based medical wastes by thermal cracking - Shahriar Bin Rasul (Nature Portfolio, 2021)
Abstract The present work is an effort to produce liquid fuel oil from plastic based medical wastes through thermal cracking process under oxidizing conditions. The mixed plastics from medical wastes were considered as a feedstock, shredded into small pieces and heated at 773 ± 10 K for 40 min with a heating rate of 20 K/min in a batch reactor for thermal cracking process. The feedstock was characterized by proximate and ultimate analysis along with thermogravimetric investigation. Moreover, chemical compositions of the liquid fuel oil were examined by FTIR and GC–MS spectroscopy. The properties of liquid product were also examined and compared to the commercial fuel oil. The average yield of brownish and sticky liquid fuel was obtained to be 52 wt% and the gross calorific value of the liquid was found 41.32 MJ/kg which is comparable to that of commercial diesel. FTIR spectrum showed characteristic absorption bands of C–H and =CH2 groups indicating presence of alkane and alkene compounds. GC–MS study demonstrated the chemical constituents of the liquid product that is mostly aliphatic compounds of mainly alkanes (16.28%), alkenes (10.67%), alcohols (14.65%) and ester groups (10.38%) including iso-phthalate (40.02%) as a predominant product. This experiment concludes that the liquid oil derived from thermal cracking of mixed plastics comprised of a composite mixture of organic components. A significant amount of non-degraded constituents like plasticizers, precursors, etc. remained in the product having some economic values with human health and environmental impacts during burning has been addressed in the current issue.